Answer:
Step-by-step explanation:
Step 1:
She Should Solve one of the equations for either x = or y = .(x and y are the variables)
Step 2:
Then Substitute the solution from step 1 into the other equation.
Step 3:
Then Solve this new equation.
Step 4:
Then Solve for the second variable.
Example 1: Solve the following system by substitution
3x+2y=6
x+y=6
Solution of example:
Step 1: Solve one of the equations for either x = or y = . We will solve second equation for y.
x+y=6
y=6−x
Step 2: Substitute the solution from step 1 into the second equation.
3x+2y=6
3x+2(6−x)=6
Step 3: Solve this new equation.
3x+2(6−x)=6
3x+12−2x=6
collecting like terms we have;
3x-2x=6-12
x= -6
Step 4: Solve for the second variable
y=6−x,since x = -6
y=6-(-6)
y= 6+6=12
The solution is: (x, y) = (-6, 12)